A study on awareness of HIV/AIDS and attitude toward people living with HIV/AIDS among engineering college students of Nellore district, Andhra Pradesh, India - Ganesan, Vijayakrishnan; Chandrasekhar, Veluru; Raghavendra, Pandurangi; Rushender, Rajan (International Journal Of Community Medicine And Public Health, 2017)
Background: AIDS is one among the complex health problems of today’s world, in the year 2014 there were 36.9 million people living with HIV. Since 2000, around 38.1 million people have become infected with HIV and 25.3 million people have died of AIDS-related illnesses. India has the third highest number of estimated people living with HIV in the world. Though the overall trend of HIV in India shows a declining trend, the HIV infected cases among adolescent age group in India is on the rise. The aim is to assess the knowledge regarding HIV/AIDS among engineering students and to assess the attitude of students towards people infected with HIV/AIDS. Methods:Cross sectional study done among 500 college students from an engineering college in Nellore district from August 2015 to September 2015. The selection of study subjects was done using convenience sampling. After consenting, each participant answered a questionnaire comprising of questions pertaining to awareness and attitude of people toward PLHA. Results: About 54% of the participants were aware that HIV can spread through body fluids such as blood, semen/vaginal fluid and breast milk and 58% knew that HIV can spread by having sex with an infected partner. About 37% of the students answered that they would not sit next to a HIV infected person on a bus and 59% of the students responded that they would divorce their spouse if they happen to know that (he/she) is infected. Conclusions:Though the study population is aware of the disease HIV/AIDS, complete knowledge about the disease, its modes of spread and protective measures is not satisfactory. It is observed that stigmatization and tendency to discriminate people living with HIV/AIDS is still present and there is no complete acceptance of positive cases by the study subjects.